2004
DOI: 10.1002/lt.20104
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density among cirrhotic patients awaiting liver transplantation

Abstract: Osteoporosis is an important and common complication in patients with chronic liver disease. The goal of this study was to determine the bone mineral density (BMD) in different subgroups among pretransplant cirrhotic patients. BMD of the lumbar vertebrae (L) and femoral neck (F) were obtained in 104 consecutive cirrhotic patients. Descriptive and inferential statistics were used to compare the BMD among various groups. The mean BMD in males (n ‫؍‬ 54) and females (n ‫؍‬ 50) at L were 1.28 ؎ 0.25 g/cm 2 and 1.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
45
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 24 publications
13
45
1
Order By: Relevance
“…Therefore, ESLD is a major risk factor for osteoporosis. The observed prevalence in patients with ESLD was consistent with previous reports (18)(19)(20).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, ESLD is a major risk factor for osteoporosis. The observed prevalence in patients with ESLD was consistent with previous reports (18)(19)(20).…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings were also seen in study done by Turkeli M et al [12] , Sokhi et al [13] and George J et al [15] in which Hepatic Osteodystrophy-An Overlooked Complication DOI: 10.9790/0853-1601055861 www.iosrjournals.org 61 | Page lumbar spine is severely affected than left hip. The probable reason behind the same findings is due to faster renewal oftrabecularbone rate than cortical bone, sites with a high proportion of trabecular bone, such as vertebrae and hips, will be affected earliest.…”
Section: Discussionsupporting
confidence: 86%
“…Similar findings were also seen in study done by Turkeli M et al [12] showedthat among 40 patients the prevalence of osteopenia and osteoporosis is 45% and 42.5% respectively. Another study conducted by Sokhi et al [13] suggested among 104 cirrhotic patients, prevalence of osteopenia and osteoporosis were 34.6% and 11.5% respectively being significantly higher in females. Auletta et al [14] conducted study among 30 patients of chronic viral hepatitis and found that the prevalence of osteopenia and osteoporosis were 44% and 20% respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Distribution of Male Osteoporosis Patients 15 bidity and mortality rates particularly after a hip fracture can be higher in men (11)(12)(13). The lifelong risk of osteoporotic fracture has been reported to be 13% in men, and one-third of all hip fractures are osteoporotic fractures (14,15).…”
Section: 90%mentioning
confidence: 99%